The Role Of Vitamin E In Reducing Bone Cancer Pain In Rat Model Of Breast Cancer-Induced Bone Pain - Baharuddin, Nur Saeida (2023)
Cancer-induced bone pain is currently facing inadequate pain management considering the unwanted side effects, relative ineffectiveness and suitability of medicine. The pain resulted from primary cancer that metastasized to bone comes with complicated mechanisms involving inflammatory and neuropathic pathway causing skeletal-related complications such as pathological bone fractures, nerve root compression and hypercalcemia of malignancy. Search for therapeutics alternative options to reduce pain and target few mechanism pathways could improve the overall survival for metastatic patients. Vitamin E as an antioxidant is widely published in bone health, anti-inflammatory, anti-cancer and anti-metastatic properties, thereby potentiate its ability in targeting cancer-induced bone pain. This study aimed to evaluate the role of vitamin E in reducing bone cancer pain in female rat model of breast cancer-induced bone pain. The rats were randomly divided into five groups of ten rats according to the experimental design. Breast cancer cell line, MDA-MB-231 at a concentration of 1 x 106 were induced into left femur of four groups namely Negative Control (NC), Alpha tocopherol (ATF), Tocotrienol Rich Fraction (TRF) and Zoledronic Acid (ZA) whereas Sham (SH) group was injected with culture media only. The rats were orally supplemented daily with 60 mg/kg alpha tocopherol for ATF group, 60 mg/kg Tocotrienol Rich Fraction for TRF group, and olive oil that serves as vehicle to SH and NC groups for 21 days. Whereas, the ZA group was dosed with 0.1 mg/kg Zoledronic Acid weekly.